DIGITAL TRANSFORMATION IN EDUCATION: A PESTEL ANALYSIS-BASED LITERATURE REVIEW IN CREATING A COMPETITIVE ADVANTAGE - Muhamad Rizal; Hardiyawan Indrayanto; Suryadi Zaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The demand to create globally competitive human resources with a competitive advantage has become an urgent need for every country. In the era of digital transformation, superior and competitive human resources serve as the most crucial foundation for the sustainability of a nation, both developed and developing countries like Indonesia. The purpose of this study is to observe, study, understand, and explain various external factors that influence the digital transformation process in education, in an effort to create adaptive, superior, and competitive human resources in today's rapid and fast-paced technological developments. This study utilizes a qualitative method with a PESTEL analysis and descriptive analytical approach to explore these matters. The secondary data used in this study is sourced from journals published within the last 5 years, educational institution publications, scientific articles, and other relevant documents. The results of this study indicate that PESTEL analysis is a technique capable of describing the impact of educational digital transformation on opportunities to create superior and competitive human resources in the future through the implementation of relevant digital technologies. Through this analysis, all macro factors influencing educational digital transformation policies—ranging from political, economic, social, technological, environmental, to legal—are analyzed to illustrate their connection to educational measures in efforts to improve student quality in order to create a competitive advantage in the world of education.